Comparison of Family Functioning, Maternal Mental Health and Maternal Coping Strategies, Between The Cases Who Are Diagnosed with Attention Deficit and Hyperactivity Disorder and The Cases Who Are Diagnosed with Intellectual Disability - Gonca Ozyurt; Yusuf Ozturk (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Aim: Comparision of family functioning, maternal mental health and maternal coping strategies, between the cases who are diagnosed with attention deficit and hyperactivity disorder (ADHD) and the cases who are diagnosed with intellectual disability (ID) and controls, was aimed in this study. Method: The study group consisted of 52 cases diagnosed with ADHD and 53 cases diagnosed with ID who are 6-12 years old. The control group (n=101) comprised patients of other clinics at hospital and was similar for gender and age to the ADHD and ID patients.. Sociodemographic form , family assessment device (FAD), general health questionnaire (GHQ), ways of coping inventory (WCI) were used to provide the data of the study. The forms were filled by mothers. Results: The sociodemographic features of cases and controls were similar. There was statistically significant difference in coping strategies and general mental health between groups. Roles, affective involvement, behaviour control subscales of family assessment device were statistically significant different between three groups while the other subscales of family assessment device were similar between groups. Conclusion: The finding, that mothers of children who are diagnosed with ADHD or ID have more difficulties in maternal mental health and maternal coping strategies and family functioning, showed that evaluating family functioning and especially maternal mental health and maternal coping strategies is as important as treating the children. [JCBPR 2016; 5(2.000): 65-74]